The implementation of Artificial Intelligence in judicial decisions in criminal proceedings - Sanchez Ronceros, Ingrid Ninón (2024)
The Artificial Intelligence (IA) is used in the criminal justice process in various ways. Firstly, it is employed to analyze large amounts of data and evidence, speeding up case reviews and the identification of relevant patterns. This can be particularly useful in detecting financial crimes, frauds, and other complex offenses. Additionally, IA can help predict the risk of a criminal's reoffending, which can influence decisions regarding parole. However, the implementation of IA in judicial decisions raises ethical and legal challenges. The lack of transparency in the algorithms used and the risk of biases are significant concerns. Furthermore, there is a debate about the role that IA should play in a judge's final decisions, as judicial decision-making often involves subjective and contextual aspects that IA may not fully comprehend. In summary, the balance between automation and human judgment remains a topic of debate in the legal community, something that I aim to elucidate in this article, given the increasing interest in this subject.